The Effect of Using Simulation Activities on Developing Algerian EFL Students’ Speaking and Listening Proficiency - CHERGUI, Karima (Journal of Human Sciences, 2016)
Crystallising Comprehension, retaining long-term outcomes, and raising the rate of interest have put extra up-to-date demands on EFL teachers. These demands have led teachers to look for recent effective innovations in language teaching. Recently, there has been much demand for the active learning techniques to encourage learners step one foot outside the stereotyped learning pattern. The need for a self-generated communication has completed the picture for teachers. By consensus, simulation came to remedy EFL learners need for communication and convey the teachers’ aim. Thus, the aim of this study was to implement the simulation activities in English language teaching to second year EFL students at University of Constantine 1. A quasi experimental method was used to test the efficacy of simulation in developing EFL learners’ speaking and listening proficiencyand a sample compromised two experimental groups participated in the study. After analysing the pre-test and post-test results, the findings revealed that simulation has successfully developed the EFL learners’ speaking and listening proficiency with greater effective impact of simulation activities on listening than on speaking proficiency.